Development of Assessment Instruments on The Personality Competence of Prospective Islamic Religious Education Teachers - Amaliyah, Amaliyah; Nurpratiwi, Suci; Effendi, Muhamad Ridwan; Wajdi, Firdaus (Proceeding International Conference on Religion, Science and Education, 2025)
The aim of the study was to develop a standardized personality competency assessment instrument for prospective religious teachers, namely meeting the minimum content and construct validity scores. Theoretically. It is important to develop an instrument for assessing the personality competence of prospective religious teachers in line with the growing demand for teachers to become role models for students. The research method uses R&D with the ADDIE model. The technique of collecting data by questionnaire and literature study. Content and construct validity data analysis techniques used the Aiken index and Confirmatory Factor Analysis through Structural Equation Modeling. The results of the study stated that the content and construct validity test of the personality competency assessment instrument for prospective religious teachers was appropriate to be used as a measure of personality competence for prospective religious teachers because all points (19) were valid. The results of the development of a personality competency measurement tool for prospective religion teachers can also be used in micro teaching lectures and can also be used by Islamic religious tutors at the elementary, middle, high school and equivalent levels when assessing the teaching skills of students who are educational apprenticesn.